Research networks and clinical trials in critical care in Brazil: Current status and future perspectives - Bozza, Fernando A. (2014)
Fundação Oswaldo Cruz. Instituto de Pesquisa Clínica Evandro Chagas. Rio de Janeiro, RJ, Brasil.